If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7+7x=-8+2(4+4x)
We move all terms to the left:
7+7x-(-8+2(4+4x))=0
We add all the numbers together, and all the variables
7x-(-8+2(4x+4))+7=0
We calculate terms in parentheses: -(-8+2(4x+4)), so:We add all the numbers together, and all the variables
-8+2(4x+4)
determiningTheFunctionDomain 2(4x+4)-8
We multiply parentheses
8x+8-8
We add all the numbers together, and all the variables
8x
Back to the equation:
-(8x)
-1x+7=0
We move all terms containing x to the left, all other terms to the right
-x=-7
x=-7/-1
x=+7
| 2j+290=950 | | -v=13.9 | | 3x-43=122 | | 5(9x+4)=3(4x+9) | | 12x-7x+5x=8(2x+1)+x-8 | | {w}{2}w2-18=-7 | | -13=-b-7 | | -f=-12.7 | | d/5=7.2 | | -f=-12.6 | | 3x+8°=2x+2° | | 15x−11=14x+7 | | -26r=208 | | -3d=-4d-5 | | -17+72=-5(x+2) | | 2=–c4 | | -18(x-9)=-324 | | 4x+2x-7=177 | | 2x+30=114 | | j/20=20 | | 12.5=2g=3.5 | | .5(3x-4)=11 | | 7x+27+60-5=180 | | 10-7g=-5-10g | | 15x+–19x−–8=–8 | | -2+16v=-26+4v | | 45x+20=12x+90 | | 2x+40=114 | | 4(3x+8)=-46+54 | | 83=n+-880 | | 3.1+10m=7.38 | | 22+6h=2(2h-3) |